Social-ecological vulnerability to climate change and risk governance in coastal fishing communities of Bangladesh - Sultana, Rumana; Irfanullah, Haseeb Md.; Selim, Samiya A.; Alam, Md. Shafiul (Frontiers in Marine Science, 2023)
In Bangladesh, fishing communities are one of the most climate-vulnerable groups, though they play an important role in economic development. The main objective of this study was to identify vulnerability by exploring exposure (i.e., lack of regulating services or household capitals), susceptibility (i.e., lack of access to provisioning services), and lack of resilience (i.e., lack of alternative livelihoods and capacity) and to explore adaptation options, and challenges to understand risk governance. The study considered 45 published research articles for analysis following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Keywords were used in combinations (e.g., fishing communities and Bangladesh; Social-ecological vulnerability and Bangladesh) to identify and screen articles from SCOPUS, Web of Science, and Google Scholar. Articles published in English focusing on vulnerability and/or risk governance, published between 2011 and 2022, featuring original empirical data or a comprehensive systematic review, and published in peer-reviewed journals were included. Articles were excluded if vulnerability and risk governance were evaluated but did not fit or match the definition used in this study. The study found frequent disasters and ocean warming caused different stresses, such as reduced fish catch and income, and resulted in an increased risk of fisheries conflict. Moreover, fishing communities have limited access to properties, modern fishing equipment, financial institutions, and fisher-centered organizations. Adaptation strategies include ecosystem-based (e.g., plantation, payment for ecosystem services) and non-ecosystem-based (e.g., temporary migration, getting help from neighbors) approaches. To boost fish production, the Government of Bangladesh instituted fishing restrictions and social safety net programs (e.g., distributing rice during the fishing restrictions); both initiatives were helpful. However, the conservation policies are not being implemented properly, and there is no particular social welfare, such as banking systems, and low-or no-interest loans being provided that may support fishers to buy fishing equipment or generate alternative income sources. Considering the previous evidence of risks, this paper recommends that fisheries conservation policies be implemented properly, and fishing communities be provided with insurance services and no-or low-interest loans. This will contribute to reducing the climateinduced social-ecological risk and improve sustainable livelihoods that can withstand any regional, national, or local crisis.